The Study of Longmuir and Frendlich Adsopption Isotherm of pd ( II) using Castor,s leaves powder - Mohamed, Mussa Mohamed Khouda; Altbiny, Zeina Fathel Mohamed; Kourtany, Krima Saed Alkhier (Journal of Pure & Applied Sciences, 2021)
Adsorption is one of the most important techniques used in addressing the problem of water pollution, for its high efficiency and simplicity of the technology used, this study addressed the phenomenon of adsorption in solutions using castor leaf powder as a material (MPCL), for the purpose of reducing the concentration of ion Pb+2 in water solutions as it is a pollutant for the aquatic environment, The adsorption process has been found to depend on a range of variables: pH, the amount of the material, primary focus, temperature and communication time. The best adsorption of Ion Pb+2 was at (PH=5, MPCL=50mg, T=288k, Tc=50min, Co=60 mg.l-1) and was a typical dish for Langmuir and Freundlich In order to study the balance process of these systems, the   Freundlich model was found to be more appropriate in interpreting these systems through R2 link coefficient values, which were (0.860) higher than the R2 value of the Langmuir, which was (0.831) The basic thermodynamic values of the adsorption process were calculated and the results were as follows (∆H°=3917.7) heat absorbent, (∆G°= -16630) automatic, (∆S°=14.278) irregular.